2014
DOI: 10.1186/2193-1801-3-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of fluoride ingestion levels, serum thyroid hormone & TSH level derangements, dental fluorosis status among school children from endemic and non-endemic fluorosis areas

Abstract: The study was undertaken to determine serum/urinary fluoride status and comparison of free T4, free T3 and thyroid stimulating hormone levels of 8 to 15 years old children with and without dental fluorosis living in an endemic and non-endemic fluorosis area. A sample group of 60 male and female school children, with or without dental fluorosis, consuming fluoride-contaminated water in endemic fluoride area of Udaipur district, Rajasthan were selected through a school dental fluorosis survey. The sample of 10 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 11 publications
2
32
0
2
Order By: Relevance
“…Our results were in concordance with the results obtained by Singh et al and Rathee et al, who also observed similar findings in their study. 6,11 In the present study, it was also observed that functional thyroid alterations were caused by high fluoride exposure, which was in correlation with the results obtained by Xiang et al 12 In a previous study conducted by Singh et al, authors comparatively evaluated the thyroid hormone levels and estimated fluoride status among pediatric subjects of age group of 8 to 15 years. Their study population comprised of two groups; endemic fluoride population, and nonendemic fluoride population.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results were in concordance with the results obtained by Singh et al and Rathee et al, who also observed similar findings in their study. 6,11 In the present study, it was also observed that functional thyroid alterations were caused by high fluoride exposure, which was in correlation with the results obtained by Xiang et al 12 In a previous study conducted by Singh et al, authors comparatively evaluated the thyroid hormone levels and estimated fluoride status among pediatric subjects of age group of 8 to 15 years. Their study population comprised of two groups; endemic fluoride population, and nonendemic fluoride population.…”
Section: Discussionsupporting
confidence: 90%
“…They concluded that it is desirable to test the fluoride content of the drinking water among with activity of thyroid hormones in pediatric subjects assessing the effect of deranged thyroid hormones on fluorosis. 6 Hosur et al, in another study, assessed the impact of fluoride-induced thyroid alterations in subjects with dental fluorosis. A total of 65 subjects with dental fluorosis from endemic fluorosis areas were included in their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, one halogen can displace another one of a higher atomic weight but cannot displace one of lower weight thereby results fluoride-thyroid-iodine antagonism which in turn lead to interference with iodine uptake 14 . In this present study out of 203 study subjects, males were 116 (57.14%) and females were 87 (42.86%).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high solubility of fluorine in water, high fluoride content in drinking water threatens the human environment. Drinking high fluorine 5 water lead to fluorosis and dental fluorosis, even cause bone sclerosis or osteoporosis, bone deformation, even paralysis and make people lose labor ability. With increasing attention about clean environment and 2 human health , technologies with high efficiency and low cost to remove the fluorine content in drinking water and wastewater are in [6][7][8] urgent demand.…”
Section: Introductionmentioning
confidence: 99%